MUHAMMADIYAH SEBAGAI KELOMPOK KEPENTINGAN DALAM POLITIK NASIONAL PASCAORDE BARU TAHUN 1998-2010 - ANDI SETIAWAN, ANDI SETIAWAN (Politika: Jurnal Ilmu Politik, 2012)
Abstract Muhammadiyah is one of Islamic organizations and even older than Indonesia itself. It is common if Muhammadiyah takes part in solving the trouble of our nation life. As an Islamic organization, Muhammadiyah has missions to carry on the good things and leave the bad things (Amar Ma’ruf Nahi Munkar), thus Muhammadiyah could not keep quiet of something happen in all aspects. As the consequence, Muhammadiyah should apply the mission in religious way whether in economic side; education in managing effort, even in the politic side there is possibly to be used as a way to apply the religious endeavor. Keywords: organization, interest group, Muhammadiyah.